Downregulated microRNA‐340‐5p promotes proliferation and inhibits apoptosis of chondrocytes in osteoarthritis mice through inhibiting the extracellular signal‐regulated kinase signaling pathway by negatively targeting the FMOD gene. Issue 1 (24th August 2018) - Zhang, Weikai; Cheng, Peng; Hu, Weihua; Yin, Weifeng; Guo, Fengjing; Chen, Anmin; Huang, Hui
Abstract : Purpose: Osteoarthritis (OA) is a degenerative joint disease that leads to the destruction of joint function. The aim of this study is to investigate the effects of microRNA‐340‐5p (miR‐340‐5p) and its target gene, FMOD,  on the proliferation and apoptosis of chondrocytes in mice with OA through the extracellular signal‐regulated kinase (ERK) signaling pathway. Materials: Twenty healthy C57BL/6J mice aged 15 months with a weight of 50 ± 2 g were selected. Ten mice were treated using a unilateral knee anterior cruciate ligament transection as well as a medial meniscectomy to establish the OA model. Besides, another 10 mice were used as the control group. Methods: A reverse transcription quantitative polymerase chain reaction and Western blot analysis methods were used to examine the expressions of related genes in cells of each group. A 3‐(4, 5‐dimethylthiazol‐2‐yl)2, 5‐diphenyl tetrazolium bromide assay and flow cytometry were also conducted to evaluate the cell function after transfection had been completed. Results: The expressions of fibromodulin (FMOD), type II collagen (Col II), B‐cell lymphoma‐2 (Bcl‐2), sex‐determining region of Y chromosome (SRY)‐related high‐mobility group‐box gene 9 (Sox9), and proliferating cell nuclear antigen (PCNA) were decreased, whereas the expressions of miR‐340‐5p, runt‐related transcription factor‐2 (Runx2), Bcl‐2‐associated X protein (Bax), and ERK1/2 were elevated in the OA mice. Downregulation of miR‐340‐5p and upregulation of FMOD decreased the expressions of Runx2, Bax, and ERK1/2, and cell apoptosis of chondrocytes, and increased the expressions of FMOD, Col II, Bcl‐2, Sox9, and PCNA, and cell proliferation. Conclusion: This study suggests that downregulation of miR‐340‐5p plays a role in promoting cell proliferation and suppressing cell apoptosis of chondrocytes in OA mice through inhibition of the ERK signaling pathway via the FMOD gene. Abstract : The downregulation of miR‐340‐5p plays a role in promoting cell proliferation and suppressing cell apoptosis of chondrocytes in osteoarthritis mice through inhibition of the extracellular signal‐regulated kinase signaling pathway via the FMOD gene.